Biomechanical effects of the medial meniscus horizontal tear and the resection strategy on the rabbit knee joint under resting state: finite element analysis - Xue, Anqi; Mao, Zuming; Zhu, Xiaoyu; Yang, Qiang; Wang, Peichen; Mao, Zimu; Du, Mingze; Ma, Xu; Jiang, Dong; Fan, Yubo; Zhao, Feng (Frontiers in Bioengineering and Biotechnology, 2023)
The biomechanical changes following meniscal tears and surgery could lead to or accelerate the occurrence of osteoarthritis. The aim of this study was to investigate the biomechanical effects of horizontal meniscal tears and different resection strategies on a rabbit knee joint by finite element analysis and to provide reference for animal experiments and clinical research. Magnetic resonance images of a male rabbit knee joint were used to establish a finite element model with intact menisci under resting state. A medial meniscal horizontal tear was set involving 2/3 width of a meniscus. Seven models were finally established, including intact medial meniscus (IMM), horizontal tear of the medial meniscus (HTMM), superior leaf partial meniscectomy (SLPM), inferior leaf partial meniscectomy (ILPM), double-leaf partial meniscectomy (DLPM), subtotal meniscectomy (STM), and total meniscectomy (TTM). The axial load transmitted from femoral cartilage to menisci and tibial cartilage, the maximum von Mises stress and the maximum contact pressure on the menisci and cartilages, the contact area between cartilage to menisci and cartilage to cartilage, and absolute value of the meniscal displacement were analyzed and evaluated. The results showed that the HTMM had little effect on the medial tibial cartilage. After the HTMM, the axial load, maximum von Mises stress and maximum contact pressure on the medial tibial cartilage increased 1.6%, 1.2%, and 1.4%, compared with the IMM. Among different meniscectomy strategies, the axial load and the maximum von Mises stress on the medial menisci varied greatly. After the HTMM, SLPM, ILPM, DLPM, and STM, the axial load on medial menisci decreased 11.4%, 42.2%, 35.4% 48.7%, and 97.0%, respectively; the maximum von Mises stress on medial menisci increased 53.9%, 62.6%, 156.5%, and 65.5%, respectively, and the STM decreased 57.8%, compared to IMM. The radial displacement of the middle body of the medial meniscal was larger than any other part in all the models. The HTMM led to few biomechanical changes in the rabbit knee joint. The SLPM showed minimal effect on joint stress among all resection strategies. It is recommended to preserve the posterior root and the remaining peripheral edge of the meniscus during surgery for an HTMM.